Determinants of house prices in Central and Eastern Europe - Balázs Égert; Dubravko Mihaljek (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper studies the determinants of house prices in eight transition economies of central and eastern Europe (CEE) and 19 OECD countries. The main question addressed is whether the conventional fundamental determinants of house prices, such as GDP per capita, real interest rates, housing credit and demographic factors, have driven observed house prices in CEE. We show that house prices in CEE are determined to a large extent by the underlying conventional fundamentals and some transition-specific factors, in particular institutional development of housing markets and housing finance and quality effects.
Keywords: E20; E39; P25; R21; R31; 330; house prices; housing market; transition economies; central and eastern Europe; OECD countries; Immobilienpreis; Wohnimmobilien; Makroökonomischer Einfluss; Schätzung; Osteuropa; OECD-Staaten